Limiares sensoriais para concentração de café conilon (Coffea canephora Pierre) no café arábica (Coffea arabica L.), perfil sensorial pela análise tempo-intensidade e percepções dos consumidores em relação à bebida - Maximino, Raphael Canal (2018)
Coffee is one of the most important cultivars in the world and Brazil is the largest producer and second largest consumer of the beverage. In the roasted and ground coffee industry, blends of arabica coffee and conilon coffee are common. However, these blends can alter and compromise the sensory quality of the product. In this sense, the Hedonic Threshold Methodology was applied to determine the compromised acceptance threshold (LAC) and the hedonic rejection threshold (LRH) and the detection threshold (LD) were also determined. In order to evaluate the alteration of the bitter taste of the blends, the time-intensity methodology was used and the methodology of the word association was used to evaluate the consumers' perception regarding coffee beverage. For the determination of LAC and LRH, coffee beverages prepared from 100% arabica coffee (control) and beverages prepared from increasing additions of conilon coffee in arabica coffee were used: 20%; 40%; 60%; 80% and 100% conilon coffee (stimulus samples). For the determination of LD the conilon coffee concentrations used were: 2.33%; 5.82%; 14.55%; 36.36% and 100%. The addition of conilon coffee in arabica coffee did not cause sensory alteration or sensory rejection of the beverage, ie, there was no significant difference (p> 0.05) between the control sample and the stimulus samples by the t test. The calculation of LD showed that from 11.05% of conilon coffee in the blend with arabica coffee consumers perceive sensory alteration in the beverage. The time-intensity analysis showed that the 100% conilon coffee presented the highest mean values in the parameters of maximum intensity (Imax), total time of stimulus duration (Ttotal) and area under the curve (area) for the attribute bitter taste. The 100% arabica sample showed the lowest averages for Ttotal and area, and did not significantly differ from the blend of 11.05% conilon coffee. The word association method showed that the coffee beverage was associated with positive terms in almost all the concepts, only the concept "arabica coffee with defective grains" was associated with negative terms. It can be concluded from the study that even if there is a change in the sensory characteristics of the arabica coffee beverage by the addition of conilon grains, the consumer does not change its acceptance of the product. Thus, it is possible to use blends of arabica and conilon coffee until the addition of 100% conilon grains.